Dual Action Antimicrobial Surfaces: Alternating Photopatterns Maintain Contact‐Killing Properties with Reduced Biofilm Formation. Issue 10 (12th October 2020) - Blackman, Lewis D.; Fros, Marion K.; Welch, Nicholas G.; Gengenbach, Thomas R.; Qu, Yue; Pasic, Paul; Gunatillake, Pathiraja A.; Thissen, Helmut; Cass, Peter; Locock, Katherine E. S.
Abstract : Front Cover : Biofouling of surfaces remains a key issue despite progress in contact‐killing and antiadhesive coatings technology. In article number 2000371 by Peter Cass, Katherine E. S. Locock, and co‐workers, alternating lowfouling polymer regions are installed onto a surface using orthogonal surface modification techniques. These dual action surfaces show significantly reduced biofouling compared to single component contact‐killing surfaces in the presence of a clinically relevant nosocomial opportunistic bacterial pathogen.